Representasi Gender dalam Film “Tenggelamnya Kapal Van Der Wijck” - Lailatul Mufarihah (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
Film is one of the mass media that influences changes in the construction of the audience's mindset. This article discusses gender that is brought back in the frame of the film